Sideways stories from Wayside School. Illus. by Dennis Hockerman. - Sachar, Louis; Hockerman, Dennis (Follett, 1978)
Humorous episodes from the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.
2.8
3-6
Keywords: Schools -- Fiction; Humorous stories; Schools -- Fiction; Humorous stories